Legal Analysis Of Siri Marriage Registration In The Family Card In The Directorate General Of Population And Civil Registration (Dukcapil) - Husna; Wahda Z. Imam; Rusdin Alauddin (LEGAL BRIEF, 2022)
Some people still carry out the practice of marriages that are not officially registered before the Marriage Registrar (PPN) and the Office of Religious Affairs (KUA) which are known as “sirri” marriages and some call them religious marriages or underhanded marriages. However, at this time through the Directorate General of Occupation and Civil Registry (DUKCAPIL) it is possible to issue Family Cards (KK) for unregistered married couples with a special mark because of the spirit of providing legal protection to citizens. Based on the issues raised above, the issue related to the juridical implications of the issuance of Family Cards for unregistered married couples becomes interesting to study. Especially in the perspective of legal harmonization between the Marriage Law and the Minister of Home Affairs Regulation. The purpose of this study was to analyze the juridical implications of registering unregistered marriages in family cards (KK) in DUKCAPIL. This type of research falls into the category of normative legal research, because it examines and analyzes normatively regulations related to legal implications as a consequence of the issuance of KK.